Pelaksanaan Pembelajaran Pendidikan Agama Islam Pada Anak Tunagrahita Tingkat SMPLB Di Sekolah Luar Biasa (SLB) Negeri 1 Bukittinggi - Nining Arianti; Salmi Wati; Zulfani Sesmiarni; Muhiddinur Kamal (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research is motivated by phenomena from the results of the researchers' initial observations about the implementation of Islamic religious education learning in mentally retarded children that the authors see. The PAI teacher in the SLB is only a general PAI teacher who has no special education for the SLB teaching profession, in the lesson plan designed in the RPP it has not been fully implemented according to plan, in the learning process it is difficult for the teacher to explain and convey material because every child must be served in a way different due to the different abilities of students, the unavailability of Islamic religious education learning books for children with special needs. This study aims to find out how to plan Islamic religious education for mentally retarded children at SMPLB Class VIII at Special School (SLB) Negeri 1 Bukittinggi and to find out how the learning process for Islamic religious education for mentally retarded children at Class VIII SMPLB at Special Schools ( SLB) Negeri 1 Bukittinggi. This study uses field research that is descriptive qualitative. Collecting data in this study by means of interviews, observation and documentation. This study used 2 informants, namely Islamic Education teachers at SMPLB level as key informants and school heads as supporting informants. Based on the results of the study it can be concluded that the implementation of PAI learning has gone well according to the plan, but the core activities are not too based on the lesson plans that have been made.